Age-Related Trends in Colon Cancer Incidence - Mahdi, Batool Mutar; Abbas, Mohammed Khalid; Dawod, Abdullah Issam; Ameer, Ahmed Majeed (Journal of Coloproctology, 2025)
Colon cancer is a malignant tumor affecting the colon, often arising from polyps. The main risk factors include age, genetics, diet, and lifestyle. It is typically characterized by rectal bleeding, altered bowel habits, and weight loss.This study will analyze the time-based and sequential trends of age-standardized cancer incidence.The cross-sectional retrospective study included 1204 patients diagnosed with colon cancer over a period extending from 2015 to 2025 at Medical City Hospital in Baghdad, Iraq.This cross-sectional study included 1204 patients with tumor of the colon, their age ranged from (14-95) years, mean ± Standard error mean was (55.97 ± 0.392). Males were 56.4% (680 cases) more than females 43.5% (524 cases) (P = 0.000). The majority fall within the 50-69 age group, with 26.81% (50-59) and 27% (60-69) of the total patients. The 30-39 and 40-49 age groups represent moderate portions of them, accounting for 7.81% and 18.18%, respectively. Younger age groups (10-29) have the lowest representation, making up only 5.14% of them.The data suggests an aging patient with colon cancer with a higher male representation across most age groups. The highest percentages were in the 50-69 years category, while younger individuals are underrepresented. The trend of a declining male to female ratio in older age groups aligns with general demographic trends, where women tend to have higher life expectancy.
Keywords: colon; age; cancer